Two new species of the genus Geocharis Ehlers, 1883 and new data on Anillina species from Portugal (Coleoptera: Carabidae) - Serrano, Artur R. M.; Aguiar, Carlos A. S. (Zootaxa, 2011)
Two new species of the genus Geocharis Ehlers, 1883 (Carabidae: Trechinae, Anillini) are described (Geocharis barcorabelo n. sp. and Geocharis antheroi n. sp.) from the northern region of Portugal (Iberian Peninsula). This work provides diagnostic characters for these species and, in particular, for the structure of male genitalia. The affinities with other known species namely their putative closest relatives, as well as ecological and biogeographical comments are also included. A key for the identification of the males of the Geocharis species found north of the Tejo River in Portugal is also provided. New chorologist data on other endogean carabids from Portugal are also included.